Structure, Optical Properties and Thermal Stability of All-Ceramic Solar Selective Absorbing Coatings: A Mini Review - Wang, Hui (Frontiers in Energy Research, 2021)
Solar selective absorbing coatings (SSAC) harvest solar energy in the form of thermal energy. Traditional metal-rich SSACs like cermet-based coatings and semiconductor–metal tandems usually exhibit both a high solar absorptance and a low thermal emittance; however, metal nanoparticles can easily oxidize or diffuse at high temperature. Different from these SSACs, the all-ceramic SSACs can keep the superior optical performance at high temperatures by restraining oxidation and metal element diffusion. Besides, the facile and inexpensive fabrication of the all-ceramic SSACs makes it possible for commercial applications. These SSACs are usually a regular combination of transition-metal carbides and nitrides, which show great thermal stability and optical properties simultaneously. The structure design of the SSACs will affect the element diffusion, element oxidation, phase transition, as well as the spectral selectivity obviously. In this article, we review the structure designs of all-ceramic SSACs, and the optical properties and thermal stability of the all-ceramic SSACs in the latest literature are also compared. The purpose of this review is to identify the optimal structure design of the all-ceramic SSAC, and we also present an outlook for the structure design strategy for all-ceramic SSACs with high photothermal conversion efficiency and thermal stability.